An Obituary - Lt Col M B Azami Breathes his Last - ., Maj Gen M H Kazmi (R) (Pakistan Armed Forces Medical Journal, 2023)
With profound grief, we learnt about the saddemise of Lt Col M B Azami. We mourn the loss of thisgreat human being and a teacher. We salute him for his most extraordinary life. His unbreakable spirit andcourage in facing adversities and physical challengeswere commendable. His true passion was to serve the ailing humanity, and he devoted himself to this causethroughout his life. He would be remembered for hisboundless generosity and unwavering principlesregardless of consequences. He was a great mentor anda model for many of us. He was the teacher of teachers and was the only person on whose recommendationFRCP (Eden) was awarded. He was kind enough to visitAFM College MH and Medical Directorate on our request, and we had the pleasure of his presence in thewards where his voice still echoes. To describe hisclinical acumen would amount to adding another hue to the rainbowMay God bless his soul, and our prayers are for the bereaved family!